Productivity of Squid Fishing Lines on Badi Island, Pangkep Regency - Ernaningsih, Ernaningsih; Jamal, Muh.; Tajuddin, Mustamin; Halifah, Halifah (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
This research was conducted in June-August 2020 in Badi Island pangkep regency of South Sulawesi province.. The research method is a case study by following directly the operation of catching 26 squid fishing rods on the capture trip. Observations were made on a squid fishing rod based in the Badi Island environment with relatively the same size and construction. Data taken 25% of the fishing population fishing fishing squid Productivity of squid fishing in each respondent is different. CPUE (Catch Per Unit Effort) value of fishing rod catch in June â€“ August has an increase in value. CPUE for the last five years of 2015-2019 has a very significant difference in value, but there are several factors that affect, among others, the efficiency of fishing gear operations, oceanography, increasing number of capture fleets and increasing number of trips. The area of capture is located around Badi Island and Lumu-Lumu Island. The time it takes to get to the arrest area is about Â± 2 hours. Potential fishing area of squid fishing rod in the waters of Badi Island Pangkep Regency supported by several aquatic oceanographic parameters namely sea surface temperature, chlorophyll-a, salinity, current speed, depth and substrak waters.